THE COMMUNITY STRUCTURE OF SEAGRASS IN ENGGANO ISLANDS, BENGKULU - Farid, M. A.; Rasidi, S.; Patria, M. P. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
The community structure of seagrass in Enggano Islands has been studied in August 2004. The aim of the study was to assess the seagrass community including species composition, density, and distribution pattern. The study was executed using transect quadrat methods, where seagrasses were counted in quadrats of 50 cm2. The result showed that the Enggano Islands seagrasses consist of seven species Enhalus acoroides, Halophila ovalis, Thallasia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, and Syringodium isoetifolium. The highest density occurred in Dua Island dominated by Thallasia hemprichii (363.3 shoots m-2), while the lowest density occurred in Merbau Island dominated by Enhalus acoroides (0.4 shoot m-2). The highest diversity index (HB) occurred in Kiape Bay (1.446) and the lowest in Merbau Island (0.634). In general, seagrass community in Enggano Islands was dominated by Thallasia hemprichii. All species has clumped distribution pattern (Id > 1).